2021
DOI: 10.1002/ente.202100112
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of NiO on Self‐Supported Co3O4 Nanoneedle Array for Electrocatalytic Methanol Oxidation Reaction

Abstract: Developing efficient transition metal oxide catalysts is still challenging for direct methanol fuel cells. Herein, an atomic layer deposition method to prepare NiO on a self-supported Co 3 O 4 nanoneedle array grown on a porous nickel foam substrate (NiO-Co 3 O 4 NA@NF) as the electrode for the methanol oxidation reaction (MOR) is reported. The synergistic effect between the NiO and Co 3 O 4 components as well as the specific 3D nanoarray structure can endow the prepared NiO-Co 3 O 4 NA@NF with a very promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In addition to these metal-doped Co 3 O 4 , related theories have been proposed in reports of mixing with other materials such as CeO 2 , 65 NiO, 66,67 carbon dots (CDs), 68 and NiCo 2 O 4 . 69 Cheng et al 66 reported their experimental exploration (Fig.…”
Section: Research Progress Of Co-based Spinel Oxides In Morsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these metal-doped Co 3 O 4 , related theories have been proposed in reports of mixing with other materials such as CeO 2 , 65 NiO, 66,67 carbon dots (CDs), 68 and NiCo 2 O 4 . 69 Cheng et al 66 reported their experimental exploration (Fig.…”
Section: Research Progress Of Co-based Spinel Oxides In Morsmentioning
confidence: 99%
“…In addition to these metal-doped Co 3 O 4 , related theories have been proposed in reports of mixing with other materials such as CeO 2 , 65 NiO, 66,67 carbon dots (CDs), 68 and NiCo 2 O 4 . 69 Cheng et al 66 reported their experimental exploration (Fig. 8 The morphology and structure of spinels also have an important influence on the catalytic activity of the material, and various forms of micro/nano-structured materials have been designed.…”
Section: Research Progress Of Co-based Spinel Oxides In Morsmentioning
confidence: 99%
“…Direct contact of the active components reduces the reaction's activation energy, and the kinetics of catalytic methanol oxidation is considerably increased. [ 168 ] Ni foams have considerable bulk and charge transport benefits as self‐supporting catalyst carriers, but their sensitivity to breakdown at high temperatures restricts their use. As a result, its alteration or surface modification is critical and warrants more investigation.…”
Section: Self‐supporting Carriersmentioning
confidence: 99%
“…Furthermore, Co-based oxides have been proved to have promotion effect on catalyzing performance. [16,17,[50][51][52][53] Shahrokhian et al synthesized a Pd-NiCoO x /C catalyst and proved that Pd-NiCoO x /C catalyst had better electrochemical activity and stability than Pd-NiO catalyst. [54] Zhang et al investigated a Pd/ Co@CoO-rGO catalyst, which showed better activity and stability than the commercial Pd/C, the commercial Pt/C, Pd/ rGO and Pd/Ni@NiO-rGO catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, researches about delafossite oxides towards electrocatalytic reactions such as oxygen reduction reaction, [48] oxygen evolution reaction [47,49] and hydrogen evolution reaction [47] have attracted extensive research interest. Furthermore, Co‐based oxides have been proved to have promotion effect on catalyzing performance [16,17,50–53] . Shahrokhian et al.…”
Section: Introductionmentioning
confidence: 99%